2016
DOI: 10.1128/jvi.02612-15
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Occurring Domestic Cat APOBEC3 Variant Confers Resistance to Feline Immunodeficiency Virus Infection

Abstract: Apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3 (APOBEC3; A3) DNA cytosine deaminases can be incorporated into progeny virions and inhibit lentiviral replication. On the other hand, viral infectivity factor (Vif) of lentiviruses antagonizes A3-mediated antiviral activities by degrading A3 proteins. It is known that domestic cat (Felis catus) APOBEC3Z3 (A3Z3), the ortholog of human APOBEC3H, potently suppresses the infectivity of vif-defective feline immunodeficiency virus (FIV). Although a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 73 publications
(120 reference statements)
4
64
0
Order By: Relevance
“…In addition, a two-domain A3Z2Z3 hybrid protein is generated through alternative splicing [70, 71]. Similar to the relationship between primate A3s and PLVs (see above), previous studies revealed that the feline A3Z3 and A3Z2Z3 proteins potently suppress the infectivity of vif -deleted FIVfca [7075] and that the Vif proteins of FIVfca (strains Petaluma, C36 and Shizuoka) counteract the antiviral action of domestic cat A3Z3 and A3Z2Z3 [71, 74]. …”
Section: A3 Antagonism By Lentiviral Vif Proteinsmentioning
confidence: 99%
“…In addition, a two-domain A3Z2Z3 hybrid protein is generated through alternative splicing [70, 71]. Similar to the relationship between primate A3s and PLVs (see above), previous studies revealed that the feline A3Z3 and A3Z2Z3 proteins potently suppress the infectivity of vif -deleted FIVfca [7075] and that the Vif proteins of FIVfca (strains Petaluma, C36 and Shizuoka) counteract the antiviral action of domestic cat A3Z3 and A3Z2Z3 [71, 74]. …”
Section: A3 Antagonism By Lentiviral Vif Proteinsmentioning
confidence: 99%
“…Although FIV has been associated with unfavourable outcomes such as opportunistic infections, neoplasia, wasting and death, the precise determinants of morbidity remain unclear. Contributory factors including viral/host genetics, age of host, viral load during acute virus infection, housing environment, stress, cohabitation with other cats and concurrent disease status have been proposed [7][8][9][10][11][12]. Efforts to control lentiviral infections primarily focus on two broad strategies: preventing new infections and suppressing viral replication in already infected individuals, both of which are particularly relevant for HIVinfected humans.…”
Section: Feline Immunodeficiency Virus (Fiv) Is a Lentivirus That Shamentioning
confidence: 99%
“…Multiple factors play roles in defining a cell's permissiveness to lentiviral infection and productive replication and include the appropriate membrane receptors for virus attachment, fusion and entry, a temporally appropriate milieu of nuclear transcription factors, activation state, target cell subset, tissue micro-environment, and presence of specific host cellular restriction factors like tetherin, APOBEC3 family and others [11,13,15,16]. These same factors also determine the identity of cells that serve as reservoirs for persistent latent virus [13].…”
Section: Feline Immunodeficiency Virus (Fiv) Is a Lentivirus That Shamentioning
confidence: 99%
“…The product was cloned into pCR2.1 vector using a TOPO TA cloning kit (Thermo Fisher Scientific) and submitted to sequencing. The A3Z3 haplotype of each sample was determined according to a previously described protocol (48) using the primers A3H2F and A3H3R and named (see the recent report [57]). Sequences were analyzed with the Geneious software (Biomatters, Auckland, New Zealand).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to HIV-1 Vif, Vifs from the HIV-2/SIV lineage counteract and induce degradation of feline A3Z2Z3 (44,47). Residues in feline A3s that are functionally involved in the interaction with FIV Vif were identified by recent studies (44,48,57). In contrast, the determinants in FIV Vif that are important for inhibition of the antiviral activity of feline A3s are poorly understood (58).…”
mentioning
confidence: 99%